When you can't pay your taxes! : how to deal with the IRS - Schriebman, Robert S. (Homewood, Ill. : Dow Jones-Irwin, 1986)
This book is about IRS collect delinquent taxes.
Includes index.
Includes bibliographical references: p. 389-390.
oo 29/08/2018, ijb 27/03/2019
Loans
Keywords: Tax collection; Tax auditing